Factors Associated With Re-Intubation Within 14 Days After Ventilator Liberation - Chu, Chia-Chen; Liu, Chin-Jung; Yen, Suh-May; Chou, Wen-Yu; Kung, Pei-Tseng; Tsai, Yuh-Show; Tsai, Wen-Chen (Respiratory care, 2017)
According to Taiwan's integrated delivery system policy, ventilator-dependent patients are successfully liberated from mechanical ventilation in accordance with step-down care. However, premature discharge affects the 14-d readmission quality index. Therefore, we explored the risk and related factors of subjects liberated from mechanical ventilation who were re-intubated within 14 d. This retrospective study analyzed a cohort of ventilator-dependent subjects 17 y of age and older using a population-based database from the Taiwan National Health Research Institutes Database from 2006 to 2010. Chi-square test and logistic regression analyses were used to explore whether subjects liberated from mechanical ventilation were re-intubated within 14 d and to investigate the related factors. A total of 15,840 ventilator-dependent subjects were liberated from mechanical ventilation, and 449 subjects were re-intubated within 14 d; the total re-intubation rate was 2.83%. The factors related to a higher risk of re-intubation were also the reasons for ventilator use, including complications, hospital accreditation level, and the ventilator weaning care stage. A higher risk of re-intubation was identified in subjects with COPD (odds ratio [OR] 1.32, 95% CI 1.02-1.7, = .035) or pneumonia (OR 1.4, 95% CI 1.07-1.86, = .02) and in subjects who stayed at a district hospital (OR 3.53, 95% CI 2.48-5.01, < .001). Liberation from mechanical ventilation in the respiratory care ward and home respiratory care were associated with the highest risk of re-intubation, which was 2.32 times that of ICU subjects ( < .001). Factors associated with re-intubation within 14 d after ventilator liberation are related to the level and quality of the care setting; thus, to prevent re-intubation, more attention should be paid to higher-risk ventilator-dependent subjects after they are liberated from mechanical ventilation.